The Spitzer extragalactic representative volume survey: The environments of high-z SDSS quasi-stellar objects - Falder, J.; Stevens, J.; Jarvis, M.; Bonfield, D.; Lacy, M.; Farrah, D.; Oliver, S.; Surace, J.; Mauduit, J.; Vaccari, M.; Marchetti, L.; González-Solares, E.; et al. (2011)
This paper presents a study of the environments of SDSS quasi-stellar objects (QSOs) in the Spitzer Extragalactic Representative Volume Survey (SERVS). We concentrate on the high-redshift QSOs as these have not been studied in large numbers with data of this depth before. We use the IRAC 3.6-4.5 μm color of objects and ancillary r-band data to filter out as much foreground contamination as possible. This technique allows us to find a significant (>4σ) overdensity of galaxies around QSOs in a redshift bin centered on z ~ 2.0 and an (>2σ) overdensity of galaxies around QSOs in a redshift bin centered on z ~ 3.3. We compare our findings to the predictions of a semi-analytic galaxy formation model, based on the ΛCDM MILLENNIUM simulation, and find for both redshift bins that the model predictions match well the source density we have measured from the SERVS data.